The Perceptual Quality of the Oculus Rift for Immersive Virtual Reality. (2nd January 2019) - Chessa, Manuela; Maiello, Guido; Borsari, Alessia; Bex, Peter J.
Abstract : The recent release of the Oculus Rift, originally developed for entertainment applications, has reignited the interest of researchers and clinicians toward the use of head-mounted-displays in basic behavioral research and physical and psychological rehabilitation. However, careful evaluation of the Oculus Rift is necessary to determine whether it can be effectively used in these novel applications. In this article we address two issues concerning the perceptual quality of the Oculus Rift. (a) Is the Oculus able to generate an acceptable degree of immersivity? In particular, is it possible to elicit the sensation of presence via the virtual stimuli rendered by the device? (b) Does the Virtual Reality experienced through the Oculus Rift induce physical discomfort? To answer these questions, we employed four virtual scenarios in three separate experiments and evaluated performance with objective and subjective outcomes. In Experiment 1 we monitored observers' heart rate and asked them to rate their Virtual Reality experience via a custom questionnaire. In Experiment 2 we monitored observers' head movements in reaction to virtual obstacles and asked them to fill out the Simulator Sickness Questionnaire (Kennedy et al., 1993) both before and after experiencing Virtual Reality. In Experiment 3 we compared the Oculus Rift against two other low-cost devices used in immersive Virtual Reality: the Google cardboard and a standard 3DTV monitor. Observers' heart rate increased during exposure to Virtual Reality, and they subjectively reported the experience to be immersive and realistic. We found a strong relationship between observers' fear of heights and vertigo experienced during one of the virtual scenarios involving heights, suggesting that observers felt a strong sensation of presence within the virtual worlds. Subjects reacted to virtual obstacles by moving to avoid them, suggesting that the obstacles were perceived as real threats. Observers did not experience simulator sickness when the exposure to Virtual Reality was short and did not induce excessive amounts of vection. Compared to the other devices the Oculus Rift elicited a greater degree of immersivity. Thus our investigation suggests that the Oculus Rift head-mounted-display is a potentially powerful tool for a wide array of basic research and clinical applications.